HUDUD IQTISODIYOTINI RIVOJLANTIRISHDA SANOAT TARMOGʻINING TUTGAN OʻRNI (Marketing Journal, 2026)
AbstractThis article analyzes the role of the industrial sector in regional economicdevelopment from both theoretical and practical perspectives. The impact of industryon regional economic growth is examined through indicators such as productionvolume, employment level, investment activity, innovation performance, and exportpotential. The research is based on regional economic theory, cluster approach, andendogenous growth theory. The findings confirm that the industrial sector serves as astrategic driver of sustainable regional development.Keywords: regional economy, industrial sector, economic growth, cluster,investment, innovation, employment, gross regional product.